THESIS: NATIONAL CORPORA AND THEIR SIGNIFICANCE IN LINGUISTICS (Ustozlar uchun, 2025)
This article examines the concept of national corpora and their growing importance in contemporary linguistics. A national corpus is defined as a large, structured, and electronically stored collection of authentic texts representing the language of a specific nation or speech community. The paper discusses the theoretical foundations of corpus linguistics, the structural components of national corpora, and notable examples from different countries. Special attention is given to the significance of corpora in linguistic research, lexicography, language teaching, sociolinguistics, translation studies, and computational linguistics. The article also highlights the challenges involved in corpus construction, such as data collection, annotation, and copyright issues. Finally, it outlines future directions for corpus development in light of technological advancements. The study demonstrates that national corpora serve as essential tools for understanding language use, guiding language policy, and fostering the development of modern linguistic technologies.